Pengaruh anggaran berbasis kinerja, sistem akuntansi keuangan daerah, sistem informasi pengelolaan keuangan daerah, dan penerapan good goverment terhadap penilaian satuan kerja perangkat daerah (studi pemerintahan di kabupaten indragiri hulu) - Rico Ales Sandra; Kennedy '; Rheny Afriana Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to examine the effect of performance-based budgeting, the financial accounting system, financial management information systems and the application of good government on performance appraisal work unit area in Indragiri Hulu.The data in this study were collected by using a survey method with the help of a questionnaire research instruments totaling 72 pieces were distributed directly to 24 working units that exist in the upstream Indragiri Hulu addressed directly to the chief financial officer, treasurer, and staff compiler financial statements work on the local work force. The data in this study will be analyzed using multiple linear regression with the help of SPSS software version 17.0. To test the validity and reliability of research instrument used Pearson correlation and Cronvach Alpha. Besides, it is also done testing data normalization using a normal probability plot.The results of this study indicate that the performance-based budgeting, the financial accounting system, financial management information systems and the application of good government and a significant positive effect on performance appraisal work unit area.Keywords: Performance-based budgeting, the financial accounting system, financial management information systems area, the application of good government, performance assessment work unit area